Informational roles and information needs of formal caregivers at child welfare institutions in Malaysia - Nurul Hazimah, Ab. Durahman; Yanti Idaya Aspura, M.K.; Noorhidawati, A. (Malaysian Journal of Library and Information Science, 2019)
This study investigates the information needs of formal caregivers of child welfare institutions through the landscape of their roles and tasks. A case study approach using purposive sampling of three children welfare institutions was conducted with a total number of 10 participants. Data were collected through a series of interviews and two focus groups. Qualitative data were analysed using NVivo. Open coding and thematic coding were used to generate themes on the informational roles and needs of the caregivers. The caregivers perform their roles as guardian, counsellor, and administrator which involve informational roles as a monitor, disseminator and spokesperson of internal and external information for the institution. Each role requires specific information in order to fulfill their tasks such as information on the children’s background, daily information required, past education, future education (including sex education) and career path, monitoring of former children, disciplinary action taken on misbehaving children, information related to sports and leisure activities, safety, health as well as children rewards. This paper is significant to this specific community (caregivers of child welfare institutions) in order to understand their information needs, based on the actual caregivers’ roles and tasks. The findings would be useful as a benchmark in providing better information services for the caregivers to perform their roles and tasks in managing children at risk.